Advancing Environmental and Health Pollution Monitoring in Medan, Indonesia: A Mechatronics-Based Meta-Analysis - Z Zumhari; Hutajulu, Elferida; Sibarani, Baringin; Sirait, Regina; Anggriani, Theresia; Matondang, Aprima A. (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Mechatronics, as an interdisciplinary field integrating mechanical, electrical, computer, and control engineering, provides innovative solutions for energy and environmental challenges in urban regions. This study conducts a systematic literature review and meta-analysis using open access datasets to evaluate solar energy potential, electricity reliability, and air quality in Medan, North Sumatra. Results show that the city has strong solar irradiance levels, averaging 5.75 kWh/m²/day, indicating substantial feasibility for photovoltaic deployment. Electricity reliability, assessed through SAIFI and SAIDI indicators, is more stable in Medan compared with other Indonesian cities, offering a favorable foundation for renewable integration. Air quality analysis reveals moderate conditions, with PM2.5 concentrations averaging 28 µg/m³, slightly above World Health Organization standards, yet lower than Jakarta and Pekanbaru. Across all dimensions, mechatronics applications, including smart grid automation, intelligent inverters, IoT-based environmental sensors, and robotics-assisted monitoring emerge as crucial tools to bridge research and implementation gaps. The study identifies limited adoption of techno-economic feasibility analysis, localized reliability assessments, and distributed sensor networks in Medan, which restricts practical deployment. Future research should emphasize mechatronic frameworks such as predictive control, cyber-physical systems, and stochastic modeling to improve resilience. Policy recommendations highlight the need for targeted incentives, pilot projects, and interdisciplinary collaboration. Overall, this work positions mechatronics as a key enabler for sustainable energy transition and environmental management in Medan, offering insights applicable to other rapidly urbanizing regions in Indonesia.